Tobacco Budworm, Heliothis virescens (Fabricius) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS)
The tobacco budworm, Heliothis virescens (Fabricius), is a native species and is found throughout the eastern and southwestern United States. It is principally a field crop pest, attacking such crops as alfalfa, clover, cotton, flax, soybean, and tobacco. Larvae bore into buds and blossoms (the basis for the common name of this insect), and sometimes the tender terminal foliar growth, leaf petioles, and stalks. This revised 6-page fact sheet was written by J. L. Capinera and published by the UF Department of Entomology and Nematology, October 2012.